A novel treatment of waste printed circuit boards by low-temperature near-critical aqueous ammonia: Debromination and preparation of nitrogen-containing fine chemicals. (1st February 2019) - Xiu, Fu-Rong; Li, Yifan; Qi, Yingying; Yu, Xuan; He, Jiahuan; Lu, Yongwei; Gao, Xiang; Deng, Yuehua; Song, Zhiqi
Highlights: We report a novel low temperature NCAA process for treatment of waste PCBs. Debromination and resource recovery were achieved simultaneously. Debromination efficiency reached 100% at 300 °C. Copper foil was efficiently recovered from waste PCBs by the NCAA process. Pyrazine and pyridine compounds were obtained for the first time from waste PCBs. Abstract: In waste printed circuit boards (PCBs), brominated epoxy resin (BER) and copper are the two types of material that attracts the most attention due to their environmental risk and resource value. In this study, a novel and high-efficiency process for debromination and resource recovery of waste PCBs by low-temperature near-critical aqueous ammonia (NCAA) was successfully developed. A batch reactor was used in experiments with the temperatures ranging from 200 to 350 °C and the reaction times from 30 to 90 min. The ammonia water in near critical conditions can act not only as a medium but also as a reactant. Approximately 100% of the Br in waste PCBs could be removed and trapped by the NCAA at 300 °C. Copper foil could be easily separated and recovered from waste PCBs after the NCAA process. No brominated organic compounds could be detected in the oil phase products after the NCAA treatment of waste PCBs even at low temperature of 200 °C. Two new products (pyrazine and pyridine compounds) with high value-added were obtained for the first time by the treatment of waste PCBs. This study provides a novel and efficient strategy for the debromination, the recovery of copper, and the preparation of high value-added nitrogen-containing fine chemicals from waste PCBs. The low-temperature NCAA processing of waste PCBs could effectively reduce the energy consumption in comparison with traditional thermal decomposition processes, and promote the sustainable waste management strategy for waste electrical and electronic equipment (WEEE).